The development of an integrative proficiency test in English for fourth year secondary school students of Nueva Vizcaya - Villar, Anita B. (1978)
This aims to develop an integrative proficiency test in English that would measure some of the receptive and productive skills particularly reading, writing and listening of 75 fourth year secondary students of Nueva Vizcaya State Institute of Technology that were randomly selected.
Appendices:: leaves 209-234
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Keywords: English language -- Examinations